A study of motivational factors of violent protest in Malamulele and Vuwani, Limpopo Province - Chabalala, Olinda, Ruth (My University, 2021)
The 1996 Constitution of the Republic of South Africa [RSA], allows people to protest, demonstrate, picket, and assemble when they believe their constitutional rights have been violated. There are legislations that have been put in place to ensure that while people are showing their dissatisfaction, they do not infringe on the rights of others by engaging in riotous behaviour. The Regulation of Gatherings Act [RGA] (Act 205 of 1993) is one of such acts. This study explored the motivations of violent protests in Malamulele and Vuwani in the Limpopo Province. A qualitative research methodology was utilised and in-depth interviews and focus group discussions were used to collect data. Purposive and snowball sampling techniques were used to sample the people who participated in the protests that occurred in the areas of this study. Thematic Content Analysis was used to analyse the findings from the in-depth interviews and the focus group discussions. The study found that the Malamulele residents were concerned about being in the Thulamela Municipality, and some of their concerns included but were not limited to employment and service delivery. This study found that in Vuwani, the violent protests were influenced by the government’s inability to effectively consult residents in the merger between Vuwani and Malamulele which was done with the intention of quenching the violent protests that had erupted in the Malamulele area. Violence is said to have occurred because the government was unresponsive, and it had failed to provide adequate services and had also made unfulfilled promises. Moreover, this study also found that people engaged in collective violence because of anger and frustration. There were also people who promoted collective violence to gain access to free grocery through looting. The destroying of government properties was seen as punishment to both the community and the government. Some protestors were emotionally disturbed when they saw buildings burning, while some children also learnt to respond with violence when in conflicting situations. The government lost money as they had to refurbish or replace things that they had already provided for. However, in comparison, the participants indicated that it is easy for the government to recover, because they only lose money while the community has to live with the scar of collective violence and its aftermath for a long time.
Thesis (Ph. D. (Criminology)) -- University of Limpopo, 2021
Keywords: Violent; Protest; Violent protest; Collective violence; Malamulele; Vuwani; Protests (Negotiable instruments); Violence -- South Africa -- Limpopo; Picketing -- South Africa -- Limpopo